The psychometric properties of the Slovenian version of the Medical Office Survey on Patient Safety Culture: Psihometrične lastnosti slovenske različice lestvice MOSOPCS za ocenjevanje kulture varnosti - Klemenc-Ketiš, Zalika; Makivić, Irena; Poplas-Susič, Antonija (Acta Medico-Biotechnica, 2021)
Purpose: Considerable differences are found between the safety of patients at the primary level of healthcare and the safety of patients at the secondary or tertiary levels. This study aimed to test the validity and reliability of the Slovenian version of the Medical Office Survey on Patient Safety Culture (MOSOPSC) in primary healthcare settings.Methods: A cross-sectional study was carried out in the largest community health centre in Slovenia, the Ljubljana Community Health Centre. We invited all employees who had a leadership function (N = 221) to participate in the electronic study, and used the Slovenian version of the MOSOPSC. We conducted confirmatory factor analysis (CFA) to examine the MOSOPSC. To determine its reliability and internal consistency, the intraclass correlation coefficient (ICC) was used. We also applied split-half methodology (the Spearman–Brown formula) and calculated the Pearson’s coefficient to assess the test-retest reliability.Results: The final sample consisted of 154 participants (69.7% response rate), of which 136 (88.3%) were female. The mean age of the sample was 46.2 ± 10.0 years. The CFA model showed good fit indices. The internal consistency of the MOSOPSC was good or very good, and Cronbach’s alpha ranged from 0.55 to 0.90. Pearson’s coefficient of temporal stability ranged from 0.540 to 0.712. The reliability, based on the Spearman–Brown formula, was good.Conclusion: The results of our study suggest that the Slovenian version of the MOSOPSC, with its original factors, could be a reliable and valid tool for measuring safety culture among primary health care workers who have a leadership role.
Keywords: patient safety; safety culture; validation studies; primary care; factor analysis